Determinants of the Quantity of Environmental Disclosure in Australian Companies - Fajarini S.W., Indah; Triasih, Arum (KnE Social Sciences, 2020)
The objective of this study is to examine the effects of company characteristics, company financial performance, and type of audit firm on environmental disclosure. The population in the study was companies listed on the Australian Securities Exchange (ASX) in year of 2017. Using purposive sampling technique, this study only select 100 companies with the highest market capitalization in Australia. Samples that met the criteria amount to 99 units of analysis. The data collection used documentation techniques. The research data analysis used descriptive statistics and inferential statistics. The results of the regression analysis show that company size and industry type have a significant positive effect on environmental disclosure. While company age, leverage, profitability, and audit firm type do not affect on environmental disclosure. Based on the results of the study, it can be concluded that the companies included in the category of sensitive industries reveal more environmental information than companies in the category of non-sensitive industries. Suggestions for further research are to use other proxies to measure company financial performance, and add or use other independent variables such as environmental performance and good corporate governance that may significantly influence environmental disclosure. Keywords: Company Age, Company Size, Leverage, Profitability, Audit Firm Type, Industry Type, Quantity of Environmental Disclosure.